SMART TALK: FOSTERING STUDENTS’ INTEREST IN LEARNING ENGLISH THROUGH A COMMUNITY-BASED GUIDANCE PROGRAM IN KARANGDORO - Ahmad Faruk; Faiqotur Rizkiyah (International Conference on Humanity Education and Society (ICHES), 2026)
English has become an essential skill in the era of globalization and digital transformation. Early exposure to English is therefore considered a strategic step in preparing younger generations to face global challenges. This article reports a community service program that provided English learning guidance for children through a community-based approach. The program, entitled SMART Talk, was conducted by lecturers and students of the English Education Department at Universitas KH. Mukhtar Syafa’at (UIMSYA) as a form of educational social contribution. It was implemented in Karangdoro Village, Banyuwangi, over three months (November 2025–January 2026) with four meetings per week. The findings showed positive outcomes. Students developed more positive attitudes toward English learning, demonstrated by punctual attendance, active participation, and responsibility in completing tasks. Their motivation increased as they showed enthusiasm and willingness to engage in activities. The friendly atmosphere also reduced English anxiety, enabling students to speak more confidently. In addition, students’ vocabulary mastery and basic speaking ability improved, as they were able to recall expressions, construct simple sentences, and perform short dialogues. The program indicates that community-based learning effectively supports English learning in rural contexts.